Assessing the effects of no-take zones in a marine protected area spanning two ecoregions and rock substrate types - Baliwe, Ndiviwe Gabriel; Pfaff, Maya C.; Branch, George M. (Frontiers in Marine Science, 2022)
This study assessed the effectiveness of no-take areas in the Table Mountain National Park MPA in protecting the biodiversity of intertidal rocky shores from impacts of harvesting. Surveys were conducted in areas of controlled harvesting and in no-take areas to compare the densities and sizes of exploited species and the community composition between shores experiencing these two levels of protection, in two ecoregions and on two types of rock substrate. Clear patterns emerged. Firstly, no-take areas had significantly greater densities of the exploited limpets Cymbula granatina, C. oculus and Scutellastra argenvillei, particularly on sandstone shores, relative to their abundance in harvested areas. Conversely, densities of the rarely harvested limpets S. cochlear, S. longicosta and S. granularis did not differ in any manner consistent with protection levels. Secondly, C. granatina and S. argenvillei were significantly larger in no-take areas, although C. oculus displayed the opposite pattern. None of the rarely harvested limpets showed consistent differences in sizes between protection levels. Thirdly, community composition differed between protection levels, particularly on sandstone shores and in the lower intertidal zones where limpets are common. No-take areas were distinguished by greater abundances of harvested limpets and mussels, while harvested areas were dominated by ephemeral and corticated algae, which flourished under reduced grazing pressure by limpets. Our study provides congruent evidence that no-take areas within this MPA are effective in maintaining a natural rocky-shore community composition, and natural densities and size structures of exploited species, testifying to the management success of no-take areas in the Table Mountain National Park, especially on sandstone shores of the Southern Benguela, where densities of harvested species are high, and harvesting is concentrated.